Role of Stocktaking Application using Barcode Scanning in Improving Stock Conformity in Hospital Pharmacy Installation - Halim, Ratna Suryati; Fitriasari, Nikma (Jurnal Kedokteran Brawijaya, 2021)
One of the most important managerial activities for hospitals is an internal control activity for drug supplies, including during the Covid-19 pandemic. A preliminary study at Graha Sehat Medika hospital (GSM hospital) showed that the inaccuracy of stocktaking results in the last six months was 40% -70%. The solution taken is the use of "SO PINTAR RS" application with barcode scanning. The purpose of this study was to determine the effectiveness of "SO PINTAR RS" application with barcode scanning in improving the accuracy of the stocktaking results at GSM hospital. The method used in this research is quasi-experimental. The data used is primary data from stocktaking activities in July-November 2020. A total of 162 drug items were used as research samples taken from the purposive sampling technique. The discrepancy between drug items in the hospital management information system (HIS) and the physical count results before and after using the application was measured in this study. The analysis of the results was carried out through nonparametric statistical tests with the Wilcoxon test. The results showed a significant difference in the results of stocktaking activities before and after using "SO PINTAR RS" application (p <0.001). The difference between the calculation results of the stocktaking with the data in the HIS decreased significantly. In addition, using this application can reduce the number of staff involved and reduce the loss of uncounted medicine items. This application is still not linked to HIS, so it is necessary to manually merge the results into HIS.